الكتاب التعليمي لمادة اللغة العربية على أساس نظرية الوحدة لطلبة معهد الحكم الإسلامي مالانج - Nadhif, Moh (UIN Maulana Malik Ibrahim Malang, 2019)
The aim of the researchers was to prepare textbooks for Arabic for elementary students in Malang al-Hikam Islamic Boarding School based on the unity theory (All in One System). The results of this study are summarized as follows: 1) Based on the results obtained by students for the first class B after the tribal and long distance test, researchers found the differences between the independent variables and dependent variables showed effective for improving Arabic and the students' ability to absorb four language skills, basic structure, preservation of archives, understanding of operations, reading comprehension, and differences between main and partial ideas. 2) Indeed the Arabic textbook designed by researchers for students Al-Hikam proved effective.